The Effect of Digital Literacy and Educational Technology on School Quality: Case Study of The Tiara Bangsa School - Abdul Canter Sangaji; Irsyad Afif Pribadi (Jurnal Penelitian Pendidikan IPA, 2023)
Poor media literacy skills will have a negative impact on the information obtained related to the truth of the information. Building awareness of media literacy will at least help in the world of education. The aim of this study is to analyze digital literacy and educational technology in quality schools at the Tiara Bangsa. This type of research is quantitative using validity techniques, frequency distribution tables, normality, linearity, and path analysis. The type of data collected was primary data which was carried out by distributing questionnaires to all employees. Tiara Bangsa School has begun to be able to apply digital literacy and educational technology together to the quality of education. The results of the study also show that digital literacy and the quality of education have not been carried out as expected. Educational Technology with the quality of Education has not been implemented properly